1990
DOI: 10.1139/v90-245
|View full text |Cite
|
Sign up to set email alerts
|

Radical clocks as probes of 1,4-biradical intermediates in the photochemical cycloaddition reactions of 2-cyclopentenone with alkenes

Abstract: ANDREAS RUDOLPH and ALAN C. WEEDON. Can. J. Chem. 68, 1590 (1990). The products of the photochemical reaction of 2-cyclopentenone with 1,6-heptadiene and with vinylcyclopropane have been examined. With 1,6-heptadiene the products were cyclobutanes, which arise from 2 + 2 photocycloaddition between the cyclopentenone carbon-carbon double bond and one of the two terminal double bonds of the heptadiene. The 1,4-biradical that is an intermediate in this reaction contains a derivative of a 1-hexenyl radical; no pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 7 publications
1
10
0
1
Order By: Relevance
“…Note added in proof Rudolph and Weedon (1990) have estimated a 50 ns lifetime for the l,Cbiradical(s) resulting from addition of cyclopentenone triplet to vinylcyclopropane, close to that for the biradical(s) of the present study.…”
Section: Discussionsupporting
confidence: 85%
“…Note added in proof Rudolph and Weedon (1990) have estimated a 50 ns lifetime for the l,Cbiradical(s) resulting from addition of cyclopentenone triplet to vinylcyclopropane, close to that for the biradical(s) of the present study.…”
Section: Discussionsupporting
confidence: 85%
“…In a study using potential radical clocks as probes in the addition to cyclopentanone, both rearranged and cyclopropane ring conserving adducts were obtained, thus supporting that 1,4-diradicals live less than 10 μs, and evidencing that photochemistry enjoys from the control on still another (beside the irradiation wavelength) further dimension, time [55]. On the other hand, the topochemical principle has been largely applied for the photochemistry in the crystals, offering a range of examples with an exquisite control of competing path, e.g.…”
Section: Ciamician and Paternò Contributionmentioning
confidence: 75%
“…In a study (see Scemes 15,16,17) based on the use of potential radical clocks, it was found that vinylcyclopropane gave an adduct with a lifetime shorter than 10 μs, while ω-pentenyl adducts essentially did not rearrange [55].…”
Section: Ciamician and Paternò Contributionmentioning
confidence: 99%
See 1 more Smart Citation
“…Χαρακτηριστικό παράδειγµα αποτελεί η περίπτωση της ανίχνευσης και παγίδευσης 1,4δίριζων ενδιαµέσων κατά τη φωτοχηµική κυκλοπροσθήκη αλκενίου στη 2-κυκλοπεντενόνη από τους Rudolph και Weedon 105. Ειδικότερα, η φωτοχηµική κυκλοπροσθήκη του βινυλοκυκλοπροπανίου στη 2-κυκλοπεντενόνη οδήγησε στ σχηµατισµό τόσο των[2+2] …”
unclassified